2015
DOI: 10.1097/md.0000000000001702
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fibrinogen and Neutrophil–Lymphocyte Ratio in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most aggressive malignancies in gastrointestinal tract cancers and even patients with early ESCC have a high metastatic potential. Difficulties are associated with clinically predicting tumor progression and prognosis based on conventional tumor markers determined from preoperative blood examinations. The aim of the present study was to measure plasma fibrinogen levels and the neutrophil–lymphocyte ratio (NLR) in blood and compare the clinical impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 29 publications
(32 reference statements)
5
77
0
Order By: Relevance
“…We previously showed that the F-NLR score is an important predictor of the progression of esophageal squamous cell carcinomas that are not treated with neoadjuvant remedies and of the prognosis of patients [16]. Hence, we speculated that the F-NLR score could serve as a novel predictor of the responses of advanced gastric cancer to chemotherapy or chemoradiotherapy and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that the F-NLR score is an important predictor of the progression of esophageal squamous cell carcinomas that are not treated with neoadjuvant remedies and of the prognosis of patients [16]. Hence, we speculated that the F-NLR score could serve as a novel predictor of the responses of advanced gastric cancer to chemotherapy or chemoradiotherapy and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We established cutoff values for plasma fibrinogen concentrations and NLR set at 400 mg/dl and 3.0, respectively, based on published reports [11,12,13,14,15,16]. The F-NLR scores were classified as 2 [both hyperfibrinogenemia (>400 mg/dl) and high NLR (>3.0)], 1 [one of these hematological abnormalities], or 0 [neither hyperfibrinogenemia nor high NLR].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have demonstrated the clinical utility of fibrinogen as a prognostic predictor in various types of malignancies 12,13. Recently, a new scoring system combining preoperative fibrinogen and the NLR (F-NLR) has been demonstrated as a promising prognostic marker for esophageal squamous cell carcinoma 14,15. However, the prognostic role of F-NLR in GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, five-year survival rates for patients with ESCC remain low at ~10%, due to the invasive and metastatic potential of ESCC (3,4). Earlier diagnosis of ESCC may reduce the probability of tumor cell metastasis and markedly improve the prognosis of patients (5,6). Therefore, the identification of novel molecular markers for ESCC has potential clinical application for the early diagnosis of patients with ESCC.…”
Section: Introductionmentioning
confidence: 99%